Knowledge and practice survey of biomedical waste management among health care workers in tertiary care hospital of Vijayapura district - Totad, Raveendra D.; Ganganahalli, Praveen (International Journal Of Community Medicine And Public Health, 2020)
Background: Biomedical waste is defined as any solid or liquid waste generated during diagnosis, treatment or immunisation of human beings and animals or during research that may present a threat of infections to humans. The Government of India had launched a law known as “Bio-medical Waste (Management and Handling) law 1998". To assess the knowledge level and status of current practice of biomedical waste management among health care workers of tertiary level teaching hospital. Methods: Cross-sectional study was conducted among health care workers like nursing staff, laboratory technicians and class-IV workers (willing to participate). Questionaries’ were asked to test the basic knowledge regarding BMW and current practices related to BMW management. Result: The knowledge level of BMW management among the health workers was around 74% whereas current practice of it among them was around 73%. The knowledge and practice of BMW management was more among nursing staff followed by lab technicians and low among class-IV workers. Conclusion: Despite of training in BMW management the awareness level and current practice of BMW handling appears to be less among class-IV workers who are exposed to it at very frequently and hence are at high risk of getting infections compared to others.